Safety, tolerability, pharmacodynamics and pharmacokinetics of DWP14012, a novel potassium‐competitive acid blocker, in healthy male subjects - Sunwoo, J.; Oh, J.; Moon, S. J.; Ji, S. C.; Lee, S. H.; Yu, K.‐S.; Kim, H. S.; Lee, A.; Jang, I.‐J. (Alimentary pharmacology & therapeutics, 2018)
Summary Background A novel potassium‐competitive acid blocker, DWP14012, is in clinical development as a potential alternative to proton pump inhibitors for the treatment of acid‐related diseases. Aims To evaluate the safety, tolerability, pharmacodynamics and pharmacokinetics of DWP14012 in humans. Methods A randomised, double‐blind, double‐dummy, placebo‐ and active‐controlled, single‐ and multiple‐ascending dose (SAD and MAD, respectively) study was conducted in healthy male subjects without Helicobacter pylori infection. Subjects randomly received a single oral dose of 10‐320 mg DWP14012, esomeprazole (active comparator) or placebo in the SAD study (n = 72) and once daily doses of 20‐160 mg DWP14012, esomeprazole or placebo for 7 days in the MAD study (n = 48; 8:2:2). Tolerability was evaluated using a microRNA‐122 assay. Pharmacodynamics were evaluated through 24‐hour gastric pH monitoring, and pharmacokinetics were evaluated plasma and urine DWP14012 concentrations. Results DWP14012 was generally well tolerated. The liver toxicity of DWP14012 was not higher than that of placebo after multiple oral administrations. DWP14012 showed rapid and sustained suppression of gastric acid secretion for 24 hours after dosing. Clear dose‐response and exposure‐response relationships were observed. Plasma concentrations of DWP14012 increased in a dose‐proportional manner in the MAD study, whereas in the SAD study, DWP14012 did not significantly accumulate in the plasma. Conclusions DWP14012 was well tolerated, and showed a rapid and long‐lasting gastric acid suppression effect in healthy subjects. These results justify further investigation of DWP14012 in patients with acid‐related disorders. Linked ContentThis article is linked to Sachs et al paper. To view this article visit https://doi.org/10.1111/apt.14864.